Evaluating the feasibility of using crystalline patterns induced by PBF-LB to predict strength enhancing orientations - José David Pérez-Ruiz; Luis Norberto López de Lacalle; Wilmer Velilla-Díaz; Jaime A. Mesa; Gaizka Gómez; Heriberto Maury; Gorka Urbikain; Haizea Gonzalez (Materials & Design)
The continuous advancement of Laser Powder Bed Fusion (PBF-LB) has expanded the possibilities of additive manufacturing, particularly in producing complex geometries. A distinctive feature of the PBF-LB process is its capacity to develop crystalline patterns, which can be utilized to predict strength-enhancing orientations of the produced components. This work presents a unified methodology and models for evaluating the feasibility of leveraging these crystalline patterns, alongside material parameters and manufacturing conditions, to predict orientations that enhance the mechanical strength of PBF-LB components. By integrating manufacturing considerations early in the mechanical design process, this framework enables the optimization of component performance through the alignment of stress fields with favorable crystalline orientations. Experimental validation through microstructural characterization and tensile testing in samples manufactured under various orientations and PBF-LB parameters demonstrated that the predicted directions for maximum and minimum mechanical strength accurately corresponded to the evaluated conditions. Notably, the 〈111〉 directions exhibited superior mechanical strength compared to the isotropic material state. This study paves the way for improving mechanical performance and broadening the market potential of PBF-LB, emphasizing its applicability across diverse industries and component types.